Mindfulness-Based Mobile Health to Address Unhealthy Eating Among Middle-Aged Sexual Minority Women With Early Life Adversity: Mixed Methods Feasibility Trial - Shufang Sun; William Nardi; Matthew Murphy; Ty Scott; Frances Saadeh; Alexandra Roy; Judson Brewer (JMIR Publications, 2023)
BackgroundSexual minority women (lesbian, gay, bisexual, pansexual, queer, and other nonheterosexual women) remain considerably underrepresented in health research despite being at a higher risk for diabetes and obesity as well as stigma and psychological distress than their heterosexual peers. In addition, early life adversity (ELA) is prevalent among sexual minority women, which further increases risks for obesity, psychological distress, and poor cardiovascular health. App-based mindfulness interventions are potentially promising for this group in mitigating the adverse health effects of ELA, reducing food craving and unhealthy eating, addressing the risks associated with obesity. ObjectiveThis mixed methods feasibility trial aimed to test a mindfulness-based mobile health approach for middle-aged sexual minority women (aged 30-55 years) with ELA and overweight or obesity (BMI ≥25 kg/m2) to improve health outcomes. MethodsThe single-arm trial was advertised on social media and various lesbian, gay, bisexual, transgender, and queer web-based groups. At baseline, after the intervention (2 months), and at the 4-month follow-up, participants completed assessments of primary outcomes (food craving, emotional eating, and weight via a mailed scale) and secondary outcomes (depression, anxiety, mindfulness, and emotion dysregulation). A standardized weight measure was mailed to participants for weight reporting. Feasibility and acceptability were assessed after the intervention via surveys and semistructured exit interviews. ResultsWe screened 442 individuals, among which 30 eligible sexual minority women (mean age 40.20, SD 7.15 years) from various US regions were enrolled in the study. At baseline, 86% (26/30) and 80% (24/30) of participants had elevated depressive and anxiety symptoms, respectively. Among the 30 enrolled participants, 20 (66%) completed all intervention modules, 25 (83%) were retained at the 2-month follow-up, and 20 (66%) were retained at the 4-month follow-up. None reported adverse effects. From baseline to the 4-month follow-up, large effects were found in food craving (Cohen d=1.64) and reward-based eating (Cohen d=1.56), whereas small effects were found with weight (Cohen d=0.20; 4.21 kg on average). Significant improvements were also found in the secondary outcomes (depression, Cohen d=0.98; anxiety, Cohen d=0.50; mindfulness, Cohen d=0.49; and emotion dysregulation, Cohen d=0.44; all P<.05). Participants with higher levels of parental verbal and emotional abuse were particularly responsive to the intervention. Participants reported that the program aligned with their goals and expectations, was easy to use, and facilitated changes in eating behavior and mental health. Barriers to engagement included the need for diverse teachers, individualized support, and body positive language. ConclusionsThis early phase feasibility trial provides proof-of-concept support for a mindfulness mobile health approach to improve obesity-related outcomes among sexual minority women and warrants a larger randomized controlled trial in the future. The findings also suggest the need to address trauma and psychological health when addressing weight-related outcomes among sexual minority women.